2014
DOI: 10.2807/1560-7917.es2014.19.48.20980
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for admission of patients with suspected Ebola virus disease in European hospitals: a survey, August-September 2014

Abstract: In response to the Ebola virus disease (EVD) outbreak in West Africa, the World Health Organization has advised all nations to prepare for the detection, investigation and management of confirmed and suspected EVD cases in order to prevent further spread through international travel. To gain insights into the state of preparedness of European hospitals, an electronic survey was circulated in August–September 2014 to 984 medical professionals representing 736 hospitals in 40 countries. The survey addressed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
(12 reference statements)
0
24
0
Order By: Relevance
“…The possibility of attending cases of Ebola (and other highly contagious infections that require high isolation) is a challenge for Western health systems. As a result, guidelines for the care and treatment of potential cases have been updated in different hospitals and countries (de Jong et al, ; Fauci, ). Furthermore, the high contagiousness of patients seeking help in hospitals makes health care workers potential victims and a source of infection.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of attending cases of Ebola (and other highly contagious infections that require high isolation) is a challenge for Western health systems. As a result, guidelines for the care and treatment of potential cases have been updated in different hospitals and countries (de Jong et al, ; Fauci, ). Furthermore, the high contagiousness of patients seeking help in hospitals makes health care workers potential victims and a source of infection.…”
Section: Introductionmentioning
confidence: 99%
“…The isolation rooms with recommended standards of negative pressure ventilation and the presence of anteroom were lower both for admitting and non-admitting EVD patients (57 % and 34 %) when compared to the survey of 48 highly infectious diseases units in 16 European countries (100 and 90 %) and also the recent survey in 14 European countries (87 and 69 % respectively). This indicates some of the global inequalities with regards to healthcare resources between North and South [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The EVD transmission cases in healthcare workers in Spain and US have demonstrated the absolute need for adequate training of healthcare workers in correct PPE donning and doffing sequences as well as in developed countries. Of note, in a recent survey of preparedness for admission of EVD patients in European hospitals, the authors identified a high proportion of hospitals (27 %) not having performed training for healthcare workers' putting on and removal of PPE through safe methods [6]. Comparable to the findings based on European hospitals (46 %), from de Jong and colleagues [6], our survey demonstrated that 49 % of admitting hospitals had plans in place for regular in-house drills, testing the systems put in place.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations